Evaluation of the Effect of Three Types of Rapid Maxillary Expanders (Conventional, Hybrid and MSE) After 6 Months in Adolescents. Randomized controlled trial - Mohamed Abdelrhman Shendy; Ahmed Abouelnour; Sara Elkabbany; Abdullah M. Alhawish; Mostafa Magdi Abdel Monem Abdel Allah; Wesameldin Rafaat Ali Gouda; Usama Thabet Ahmed; Ibrahim Saad Abd El-Ghafar; Khaled Mohammad Taha; Abubakr Mohammed Fouad; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives:The purpose was to asses and analyze the resultant efficacy of three different maxillary expanders (conventional, hybrid, and MSE) on adolescent maxilla utilizingthree dimension dental x ray hence cone beam computed tomography (CBCT) was the proper choice. Material and Methods: The trial wasbased on three groups, and the net sample was made up of 46 healthy 11–16-year-olds (17 girls and 29 boys). Patients were allocated to groups with the aid of sequentially numbered, opaque sealed envelopes (SNOSE). Group A received conventional hyrax appliance (CH) (5 girls, 10 boys),miniscrew assisted rapid palatal expansion (MARPE)was used with two different design in the other two groups, hence, Group B used hybrid hyrax appliance with two anterior palatal miniscrews (HH) (6 girls, 9 boys), and Group C had the maxillary skeletal expander (MSE) (6 girls, 10 boys). Using Anatomage in vivo 5.19, Dental and skeletal parameters change were assessed for each group at base line (T1) and after expansion(T2), based on 92 CBCT scans. Results: ANOVA was used to compare normally distributed numerical variables between groups, and when a difference was shown to be significant, the post hoc test (Bonferroni) was used. In CH , 73.3% of cases were bilateral, in comparison to 53.3% and 56.3% bilateral cases in HH and MSE respectively; with no significant difference between groups (p=0.477),when comparing the type of malocclusion class in CH and HH, 73.3% of cases were class 3, in comparison to 75% class 3 cases in MSE; with no significant difference between groups (p=0.993). Conclusion:After expansion, all kinds performed well; however, as compared to the conventional hyrax appliance, the MARPE, and particularly the MSE, had stronger skeletal impact and less buccal tilting.